Wetland disturbance level and macrophyte composition in natural wetlands and paddy fields in the eastern part of Lake Tana, Ethiopia - Aklilu Agidie; Ayalew Wondie; Getachew Beneberu (Heliyon)
Natural wetlands and paddy fields support a rich diversity of life forms. The study objective includes assessing the macrophyte community in relation to environmental variables and providing information on floristic compositions. The research is significant for determining the extent of disturbance and potential remedies from the standpoint of the health of the wetland ecosystem. Macrophytes were sampled and water quality parameters were measured from 20 sites across five wetlands. Cluster analysis grouped the sites into three categories based on their level of disturbance. An ordination method was employed to elucidate the gradients and relationships between environmental factors and species assemblages. Agricultural activities in the area disrupt wetland ecosystems, significantly altering vegetation composition and reducing biodiversity. These changes were primarily driven by variations in water quality and nutrient levels. In total, 37 macrophyte species were recorded in natural wetlands, while 33 species were identified in paddy fields. Key species, including Digitaria sanguinalis, Phalaris paradoxa, and Echinochloa stagnina, served as crucial animal fodder, while Cyperus papyrus and Typha latifolia supported the subsistence livelihoods of local communities. Dilmo Wetland exhibited the highest species richness in both natural wetlands (S = 29) and paddy fields (S = 21). The greatest Shannon-Wiener index values were observed at Dilmo Wetland, with H′ values of (2.91) in natural wetlands and (2.67) in paddy fields, while Shesher Wetland had the highest dominance index (D = 0.28). Current research has shown that wetlands near the Lake Tana littoral zone faced the most severe disturbances due to human activities, seasonal flooding, and invasive species (Eichhornia crassipes), which caused significant declines in biodiversity. To preserve the biodiversity and ecosystem health in floodplain areas, implementing sustainable wetland management interventions is essential.